Effects of Financial Literacy, Risk Tolerance, and Herding on Gen Z IPO Decisions Moderated by Prospectus Information - Sukmawati, Ayu; Prabowo, Heri; Widiastuti, C. Tri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of financial literacy, risk tolerance, and herding behavior on the investment decisions of Generation Z in IPO stocks, with prospectus information serving as a moderating variable. The research adopts a quantitative approach involving 180 Gen Z investors in Semarang City who purchased IPO stocks during the period of 2023 to 2025. Data were collected through a structured questionnaire and analyzed using SmartPLS version 4 to assess both the measurement model and the structural model. The findings reveal that financial literacy and herding behavior do not exhibit a significant direct effect on investment decisions. In contrast, risk tolerance shows a positive and significant influence, indicating that individuals with a higher ability to accept risk tend to make more decisive investment choices in IPO stocks. Furthermore, prospectus information does not moderate the relationship between financial literacy or risk tolerance and investment decisions, suggesting that the availability of information does not necessarily enhance the impact of these variables. Interestingly, prospectus information is found to strengthen the influence of herding behavior on investment decisions. This indicates that when investors are exposed to clear, detailed, and credible information, their tendency to follow the actions of the majority becomes more pronounced. Overall, the study highlights that psychological aspects, particularly risk tolerance play a crucial role in shaping Gen Z’s investment behavior, while informational factors may interact differently depending on the nature of the investor's behavioral tendencies.